Multiplicative background risk - Günter Franke; Harris Schlesinger; Richard C. Stapleton (University of Konstanz, Center of Finance and Econometrics (CoFE), 2003)
Although there has been much attention in recent years on the effects of additive background risks, the same is not true for its multiplicative counterpart. We consider random wealth of the multiplicative form xy, where x and y are statistically independent random variables. We assume that y is endogenous to the economic agent, but that is an exogenous and nontradable background risk, which represents a type of market incompleteness. Our main focus is on how the presence of the multiplicative background risk y affects risk-taking behavior for decisions on the choice of x. We characterize conditions on preferences that lead to more cautious behavior.
urn:nbn:de:bsz:352-opus-10089
Keywords: D81; 330; multiplicative risk; background risk; incomplete markets; standard risk aversion; affiliated utility function; multiplicative risk vulnerability; Erwartungsnutzen; Nutzenfunktion; Risikopräferenz; Theorie